Identification and activation of TLR4-mediated signalling pathways by alginate-derived guluronate oligosaccharide in RAW264.7 macrophages - Weishan Fang (Nature Portfolio, 2017)
Abstract Alginate, a natural acidic polysaccharide extracted from marine brown seaweeds, is composed of different blocks of β-(1, 4)-D-mannuronate (M) and its C-5 epimer α-(1, 4)-L-guluronate (G). Alginate-derived guluronate oligosaccharide (GOS) readily activates macrophages. However, to understand its role in immune responses, further studies are needed to characterize GOS transport and signalling. Our results show that GOS is recognized by and upregulates Toll-like receptor 4 (TLR4) on RAW264.7 macrophages, followed by its endocytosis via TLR4. Increased expression of TLR4 and myeloid differentiation protein 2 (MD2) results in Akt phosphorylation and subsequent activation of both nuclear factor-κB (NF-κB) and mechanistic target of rapamycin (mTOR). Moreover, GOS stimulates mitogen-activated protein kinases (MAPKs); notably, c-Jun N-terminal kinase (JNK) phosphorylation depends on TLR4 initiation. All these events contribute to the production of inflammatory mediators, either together or separately. Our findings also reveal that GOS induces cytoskeleton remodelling in RAW264.7 cells and promotes macrophage proliferation in mice ascites, both of which improve innate immunity. Conclusively, our investigation demonstrates that GOS, which is dependent on TLR4, is taken up by macrophages and stimulates TLR4/Akt/NF-κB, TLR4/Akt/mTOR and MAPK signalling pathways and exerts impressive immuno-stimulatory activity.